Novelties in Begonia (Begoniaceae) from the campos rupestres of Serra do Padre Ângelo, Minas Gerais, Brazil: a new species and a new record - Kollmann, Ludovic Jean Charles; Gonella, Paulo Minatel (Phytotaxa, 2021)
Begonia piranga (Begoniaceae) is a new narrowly endemic species from the campos rupestres of Serra do Padre Ângelo, a quartzitic massif in Conselheiro Pena, eastern Minas Gerais state, Brazil. Description, diagnosis, taxonomic comments, detailed illustrations, field photographs, and a provisional IUCN Red List Assessment are provided. The new species is considered Critically Endangered due to its restricted occurrence in high elevation rock outcrops, small population size, and decline in the quality of the habitat. Begonia vasconcelosiana, another Critically Endangered species, is also newly reported here for Serra do Padre Ângelo. These discoveries add to the increasing list of novelties from Serra do Padre Ângelo, reinforcing the urge for conservation actions to protect the endemic flora of this Serra and other areas of campos rupestres in eastern Minas Gerais state.